Factorise - 12x + 36

-12x + 36

12 is common b/w these two terms

we take 12 positive.

so, 12( -x + 3 ) ANSWER

  • 3

factors of -12x = -2*2*3*x

factors of 36 = 2*2*3*3 

we'll take 2*2*3 as common

12 (-x+3)

  • 1

IF IT IS THIS

12x + 36

12 is common b/w these two terms

 

so, THE term can be written in factorisatio as

12( x + 3 ) ANSWER

  • 2

12{-x+ 3}

  • 0

12x + 36 = 12(x+3)

  • 0

-12x  +  36 =12( -x + 3)


  • 0

I HELP YOU AND WANT TO CLEAR YOUR QUERRY BUT YOU GIVE THUMBS DOWN

  • 0

 12x+36=12(x+3)

  • 0

 i did'nt give u thumbs down.....its sum1 else...infact i came here now nd u r blaming me....and i wanted the ans. i npositive as u have given....

  • 3
What are you looking for?